Impact of the laser scanning strategy on the quality of 17-4PH stainless steel parts manufactured by selective laser melting - Sara Giganto; Susana Martínez-Pellitero; Joaquín Barreiro; Paola Leo; Mª Ángeles Castro-Sastre (Journal of Materials Research and Technology, 2022)
A significant correlation between scanning strategies and the quality of parts manufactured additively with Selective Laser Melting (SLM) technology is shown. Therefore, a in deep study of the influence of scanning strategy is of great value for the manufacturing process in order to promote SLM technology in applications with high service requirements. In particular, this research is carried out on 17-4PH stainless steel parts, which is an alloy widely used in sectors such as aerospace or automotive for its excellent mechanical properties. This research proposes to evaluate the properties of 17-4PH parts manufactured using three usual scanning strategies (normal, concentric and hexagonal) in order to optimize the SLM process depending on the final part application. According to the obtained results, the following general conclusions have been drawn. Hexagonal strategy can be considered the most appropriate in terms of porosity. Both hexagonal and normal strategy have good mechanical properties, as well as geometrical and dimensional quality. Regarding surface finish of top face (where the used scanning pattern is visible), normal strategy is the most appropriate. In general, concentric strategy presents different results from the others: larger and irregular pores, ductile tensile behaviour, low roughness on lateral faces, and high geometrical errors in samples with large scanning vectors. As a future work, it is proposed to manufacture SLM parts combining these strategies in order to improve their properties. In addition, it is proposed to evaluate the influence of different post-process operations on the quality of parts printed by SLM using different strategies.